Ligase-Independent Cloning of Amylase Gene from a Local Bacillus subtilis Isolate and Biochemical Characterization of the Purified Enzyme - Ozturk, Merve Tuzlakoglu; Akbulut, Nagihan; Ozturk, Saliha Issever; Gumusel, Fusun (Springer, 2013)
Five hundred ninety-seven bacterial isolates from Turkish hot spring water sources were screened for their ability to produce extracellular alpha-amylase. Among them, a high enzyme-producing Bacillus subtilis isolate, A28, was selected, and its alpha-amylase gene was cloned and expressed in Escherichia coli by a ligase-independent method. alpha-Amylase from the recombinant strain was purified to homogeneity by Q-Sepharose anion exchange and Sephacryl S-100 gel filtration chromatographies. The final yield of the enzyme was about 22.5 % of the initial activity, with a 16.4-fold increase in specific activity compared with the culture lysate. The optimum temperature and pH of the enzyme were 70 A degrees C and 6.0, respectively. The enzyme was highly active at acidic-neutral pH range of 4.5-7.0. The amy28 alpha-amylase retained 100 % of its activity after incubation at 50 A degrees C for 90 min. Co+2, Cu2+, Fe2+, Fe3+, Ni+2, and Zn+2 caused significant inhibition in enzyme activity, which was not affected by Na+, Mg2+, Li+, and Ba2+. The activity was inhibited about 70 % upon treatment of the enzyme with 10 mM ethylenediaminetetraacetic acid. However, Ca2+ ions known as high temperature stabilizer for other amylases did not stimulate the activity of the enzyme. Due to pH stability and thermostability of the recombinant amylase, this enzyme may be suitable in starch processing, brewing, and food industries.
Keywords: alpha-Amylase; Bacillus; Ligation-independent cloning; Purification; Biochemical characterization